(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
The rapid development of digital technologies has significantly transformed the tourism industry, leading to the emergence of innovative service management approaches. Artificial intelligence (AI) technologies play a crucial role in improving operational efficiency, customer interaction, and service personalization within tourism organizations. Among various AI applications, chatbots have become an effective tool for enhancing communication between tourism service providers and tourists. This study examines the role of AI-powered chatbots in tourism service management and their potential contribution to improving the efficiency of tourism services in Uzbekistan. The research analyzes the main advantages of chatbot technologies, including real-time customer interaction, automated service processes, cost reduction, and improved service quality. The study also explores international experiences of implementing chatbot technologies in tourism services and evaluates their applicability in the context of Uzbekistan’s tourism sector. The findings indicate that AI-powered chatbots can significantly improve tourism service efficiency by reducing response time, increasing customer satisfaction, and optimizing operational processes. The study concludes that the integration of chatbot technologies into tourism service systems can support digital transformation and enhance the competitiveness of tourism services in Uzbekistan.